China Satellite Navigation Conference (CSNC) 2019 Proceedings Volume II - Sun, Jiadong; Yang, Changfeng; Yang, Yuanxi (Lecture Notes in Electrical Engineering,, 2019)
China Satellite Navigation Conference (CSNC) 2019 Proceedings presents selected research papers from CSNC2019 held during 22nd-25th May in Beijing, China. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 12 topics to match the corresponding sessions in CSNC2019, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.